DAMPAK LINGKUNGAN KERJA DAN STRESS KERJA TERHADAP PRODUKTIVITAS KERJA MELALUI MOTIVASI PEGAWAI - Lucky, Plori Tri; Utari, Woro; Indrawati, Mei (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
The aim of the research is to describe and analyze the influence of the work environment and work stress on work productivity through motivation. This type of research is explanatory research with a quantitative approach. The population in this study were all employees of ASN Public Works Department of Highways and Spatial Planning Bojonegoro as many as 70 people. The sample size is also 70 people with total sampling technique. This study uses PLS-SEM analysis. Based on the results of the study, it was found that productivity, motivation and work environment were in the high category, only work stress was in a fairly high condition. Work environment has a significant positive effect on employee motivation. Work stress on motivation does not have a significant effect. Work environment has a significant influence on productivity. Work stress has no significant effect on productivity. Motivation on Productivity has a significant influence. Work environment on Productivity through Motivation has a significant influence. Work stress on productivity through motivation has no significant effect.